RNA:DNA hybrids are a novel molecular pattern sensed by TLR9 - Rigby, Rachel E (Blackwell Publishing Ltd, 2014)
The sensing of nucleic acids by receptors of the innate immune system is a key component of antimicrobial immunity. RNA:DNA hybrids, as essential intracellular replication intermediates generated during infection, could therefore represent a class of previously uncharacterised pathogen-associated molecular patterns sensed by pattern recognition receptors. Here we establish that RNA:DNA hybrids containing viral-derived sequences efficiently induce pro-inflammatory cytokine and antiviral type I interferon production in dendritic cells. We demonstrate that MyD88-dependent signalling is essential for this cytokine response and identify TLR9 as a specific sensor of RNA:DNA hybrids. Hybrids therefore represent a novel molecular pattern sensed by the innate immune system and so could play an important role in host response to viruses and the pathogenesis of autoimmune disease.